Highly fluorescent aryl-cyclopentadienyl ligands and their tetra-nuclear mixed metallic potassium–dysprosium clusters. Issue 65 (30th October 2020) - Arumugam, Selvakumar; Reddy, Pulikanti Guruprasad; Francis, Maria; Kulkarni, Aditya; Roy, Sudipta; Mondal, Kartik Chandra
Abstract : Alkyl substituted triaryl-cyclopentadienyl ligands with aggregation-induced emission enhancement (AIEE) properties and their applications in the syntheses of novel chloride bridged tetra-nuclear mixed potassium–dysprosium metallocenes. Abstract : Two alkyl substituted triaryl-cyclopentadienyl ligands [4, 4′-(4-phenylcyclopenta-1, 3-diene-1, 2-diyl)bis(methylbenzene) (1 ) and 4, 4′, 4′′-(cyclopenta-1, 3-diene-1, 2, 4-triyl)tris(methylbenzene) (2 )] have been synthesized via cross-aldol condensation followed by Zn-dust mediated cyclization and acid catalyzed dehydration reactions. The fluorescence properties of 1 and 2 have been studied in solution and solid state. The ligands exhibited aggregation-induced emission enhancement (AIEE) in THF/water solution. 1 and 2 have been found to be significantly more fluorescent in the solid state than in their respective solutions. This phenomenon can be attributed to the strong intermolecular CH⋯π interactions present in 1 and 2 which leads to the tight packing of molecules in their solid-state. Both 1, 2 and their corresponding anions have been studied by theoretical calculations. Ligands 1 and 2 have been shown to react with anhydrous DyCl3 in the presence of potassium metal at high temperature to afford two fluorescent chloride-bridged tetra-nuclear mixed potassium–dysprosium metallocenes [(Me2 Cp)4 Dy2 III Cl4 K2 ]·3.5(C7 H8 ) (5 ) and [(Me3 Cp)4 Dy2 III Cl4 K2 ]·3(C7 H8 ) (6 ), respectively in good yields.